Gender inequalities in health among workers: the relation with family demands. Issue 9 (1st September 2001) - Artazcoz, L; Borrell, C; Benach, J
Abstract : OBJECTIVES: To analyse whether there are gender inequalities in health among male and female workers who are married or cohabiting and to assess whether there are gender differences in the relation between family demands and health. Additionally, for both objectives it will be examined whether these gender patterns are similar for manual and non-manual workers. DESIGN AND SETTING: The data have been taken from the 1994 Catalonian Health Survey (CHS), a cross sectional survey based on a representative sample of the non-institutionalised population of Catalonia, a region in the north east of Spain that has about 6 million inhabitants. The dependent variables were four ill health indicators (self perceived health status, limiting longstanding illness, having at least one chronic condition and mental health) and two health related behaviours closely related to having time for oneself (no leisure time physical activity and sleeping six hours or less a day). Family demands were measured with three variables: household size, living with children under 15 years and living with adults older than 65 years. The analysis was separated for gender and social class (manual and non-manual workers) and additionally adjusted for age. Gender differences for all dependent and independent variables were first tested at the bivariate level using the χ 2 test for categorical variables and the t test for age. Secondly, multivariate logistic regression models were fitted. PARTICIPANTS: Persons who were employed, married or cohabiting, aged 25 to 64 years (2148 men and 1185 women). RESULTS: A female excess for all the ill health indicators was found, while there were no gender differences in the health related behaviours analysed. Family demands had a greater impact on health and health related behaviours of female manual workers. In this group household size was positively related to four dependent variables. The adjusted odds ratios (ORs) to living in family units of more than four persons versus living only with the spouse were 2.74 (95%CI=1.22, 6.17) for poor self perceived health status, 3.16 (95%CI=0.98, 10.15) for limiting long standing illness, 3.28 (95%CI=1.45, 7.44) for having at least one chronic condition, and 2.60 (95%CI=1.12, 6.00) for sleeping six hours or less a day. Among female manual workers living with children under 15 years was positively associated with no leisure time physical activity (adjusted OR=2.37; 95% CI=1.43, 3.92) and with sleeping six hours or less a day (adjusted OR=1.91; 95% CI=1.13, 3.32). Living with adults older than 65 years had an unexpected negative relation with poor self perceived health status (adjusted OR=0.33; 95%CI=0.16, 0.66), and with chronic conditions (adjusted OR=0.45; 95%CI=0.24, 0.87) in female manual workers. Among male manual workers living with children under 15 years was positively associated with longstanding limiting illness (adjusted OR=2.44; 95%CI=1.36, 4.38). CONCLUSION: When gender differences in health are analysed, both the paid and the non-paid work should be considered as well as the interaction between these two dimensions, gender and social class. In Catalonia, as probably in Spain and in other countries, private changes such as sharing domestic responsibilities, as well as active public policies for facilitating family care are needed in order to reduce gender health inequalities attributable to the unequal distribution of family demands.